2006
DOI: 10.1007/s00401-006-0167-4
|View full text |Cite
|
Sign up to set email alerts
|

The brain-specific protein TPPP/p25 in pathological protein deposits of neurodegenerative diseases

Abstract: Immunohistochemical detection of protein components of pathological inclusions is widely used for neuropathological diagnosis of neurodegenerative disorders. However, different antibodies and antigen unmasking methods may account for variability between research studies and thus may affect diagnostic accuracy. Using two different antibodies raised against either a segment (184-200 aa) or the full length of human recombinant brain-specific tubulin polymerization promoting protein TPPP/p25, we immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…We also confirmed the results of previous studies describing that the immunoreactivity of TPPP was markedly decreased in the peripheral processes of MSA-oligodendroglia, whereas TPPP was increased in the swollen perinuclear cytoplasm of some MSAoligodendroglia [8,11,12,27,34,35]. These observations indicate that TPPP not only relocates from the terminal processes that normally form the myelin sheath, but also translocates from the nucleus and focally accumulates in the swollen perinuclear cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…We also confirmed the results of previous studies describing that the immunoreactivity of TPPP was markedly decreased in the peripheral processes of MSA-oligodendroglia, whereas TPPP was increased in the swollen perinuclear cytoplasm of some MSAoligodendroglia [8,11,12,27,34,35]. These observations indicate that TPPP not only relocates from the terminal processes that normally form the myelin sheath, but also translocates from the nucleus and focally accumulates in the swollen perinuclear cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…This marker provides robust results in formalin-fixed paraffin-embedded tissue; its antigenicity is preserved even after prolonged fixation in routinely used fixatives and has been successfully used in previous studies [17,18,19,20,21]. Apart from neurons, oligodendrocytes are considered to be the other major cell type having pTDP-43-immunoreactive inclusions in TDP-43 proteinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated that pTDP-43-immunoreactive inclusions colocalize with TPPP/p25, and, therefore, we confirmed that the cells containing the inclusions are indeed oligodendrocytes. The partly overlapping immunoreactivity could suggest a redistribution of cytoskeletal elements into the glial inclusions, reminiscent of the inclusions in the α-synucleinopathy called multiple system atrophy [18,19]; however, this merits further analysis. As with neurons, the majority of pTDP-43-immunoreactive inclusions in oligodendrocytes was ubiquitinated and contained p62.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early myelin alterations in MSA brains have been demonstrated recently by the presence of altered myelin basic protein and p25alpha [205]. The p25alpha protein, also called tubulin polymerization promoting protein (TPPP), has been shown to colocalize with alphasynuclein-positive CGIs and to abnormally accumulate in MSA oligodendrocytes [68,87,98,168]. Transfer of p25alpha to oligodendroglial cell bodies has also been detected in early MSA, suggesting that this event causes myelin damage followed by alpha-synuclein aggregation and secondary neurodegeneration [168,205].…”
Section: Neuropathologymentioning
confidence: 95%